MENANAMKAN NILAI KEIMANAN DENGAN METODE BERMAIN PERAN TOKOH AGAMA DALAM UPAYA MENINGKATKAN PRESTASI BELAJAR AGAMA HINDU - Jelantik, I Gusti Lanang (LPPM IKIP PGRI Bali, 2019)
The purpose of conducting this class action research is to improve the learning achievement of students of class IX-4 in semester I of the 2018/2019 academic year at SMP Negeri 6 Denpasar. This research was conducted on 41 research subjects. The way to do this is to add old conventional learning styles into new learning methods that are discovery using the use of the question have strategy (questions raised by students themselves). The study was conducted in two cycles, each cycle carried out with the stages of planning, implementation, observation and reflection. To collect data on the results of research used learning achievement tests and to analyze the data used descriptive analysis. Judging from the results of evaluations that have been carried out an increase from the initial data with an average of 76.12 with mastery learning 36.59%, in the first cycle the average increased to 79.51 with mastery learning 75.61% and in the second cycle increased again to 83.54 with 100% mastery learning. Thus it can be concluded that the use of the question have strategy (questions raised by students themselves) can improve learning achievement in English.